Acute Oral Toxicity and Organ Safety Assessment of Rutin in Sprague Dawley Rats in Accordance with OECD Test Guideline 425 - Archana, A.; Benny, Angel; John, Preethy; Nisha, A. R.; Raji, K.; Anoopraj, R.; Nair, S. N. (International Journal of Bio-resource and Stress Management, 2026)
The study was conducted during the month of June, 2025 at College of Veterinary and Animal Sciences, Mannuthy, Thrissur, Kerala, India to investigate the acute oral toxicity profile of rutin, a naturally occurring flavonol glycoside, in female Sprague Dawley rats in accordance with OECD Guideline 425 at a limit dose of 2000 mg kg-1 body weight. Animals were monitored for fourteen days for mortality, clinical signs, general systemic parameters, biochemical changes, antioxidant status, relative organ weights, and histopathological alterations. No mortality or overt signs of toxicity were observed. Rutin treated rats exhibited comparatively lower body weight gain than controls, more evident during the second week, while feed and water intake remained unaffected and within normal physiological limits. No significant variation in serum ALT or AST was not observed. Renal function indices, like BUN and creatinine did not differ significantly from control values. A significant increase in relative liver weight was noted in the treated group, with no significant changes in other organs. Antioxidant assessment demonstrated a significant increase in superoxide dismutase activity in cardiac tissue and a significant reduction in hepatic lipid peroxidation, while catalase activity and reduced glutathione levels in heart and liver remained comparable to controls. Histopathological evaluation revealed no hepatic lesions and no marked pathological changes in other examined organs. Collectively, these findings indicated that oral administration of rutin at 2000 mg kg-1 did not produce acute systemic toxicity and was associated with measurable antioxidant effects, supporting its relative safety following single dose oral exposure.